2012
DOI: 10.1007/s11136-012-0132-8
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction in patients with chronic musculoskeletal pain and its predictors

Abstract: Life satisfaction in patients with chronic musculoskeletal pain and its predictors Boonstra, Anne M.; Reneman, Michiel F.; Stewart, Roy E.; Post, Marcel W.; Preuper, Henrica R. Schiphorst Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. Abstract Purpose To determine the life satisfaction of patients with chronic non-malignant musculoskeletal pain (CMP) compared to the general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 26 publications
3
19
0
2
Order By: Relevance
“…While there were no group differences with respect to descriptive data for age, anthropometrics or grip strength, the WAD group scored significantly poorer than the controls for both the physical and mental component summary scales of the SF-36, reflecting limitations in physical ability and psychological distress. Such reductions in scores of SF-36 seem to be a common finding in people with chronic musculoskeletal diseases [61,62]. The control group scored about the same as the Norwegian normative values for both the physical and mental component summary scales of the SF-36.…”
Section: Discussionmentioning
confidence: 71%
“…While there were no group differences with respect to descriptive data for age, anthropometrics or grip strength, the WAD group scored significantly poorer than the controls for both the physical and mental component summary scales of the SF-36, reflecting limitations in physical ability and psychological distress. Such reductions in scores of SF-36 seem to be a common finding in people with chronic musculoskeletal diseases [61,62]. The control group scored about the same as the Norwegian normative values for both the physical and mental component summary scales of the SF-36.…”
Section: Discussionmentioning
confidence: 71%
“…Studies report that individuals in older age groups had more pain problems. 25,26 The reason for women experiencing more pain has been an important discussion and analysis topic in the literature. A comprehensive review study on this issue reported that this case was associated with various factors, such as women expressing their pain more easily, their anatomical and fertility features, and lifestyle and sociocultural features.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain markedly decreases individuals’ health status and quality of life (QoL) [10,11,28-31] and can detrimentally affect the families of patients [32]. The degree of this effect is grossly underestimated.…”
Section: Introductionmentioning
confidence: 99%